The split tibialis anterior muscle flap - A simple solution for longitudinal middle third tibial defects - Nikhil Panse; Parag Sahasrabudhe; Ganesh Pande; Ajay Chandanwale; Rajendra Dhongde; Lalit Rajpal (Indian Journal of Plastic Surgery)
Background: The tibialis anterior flap is an underused flap, mainly because it is not an expendable muscle and is small in size. Aim: To study the use of the tibialis anterior muscle flap for longitudinal middle third tibial defects. Materials and Methods: We have analysed the use of tibialis anterior flap in five patients by the function preservation technique. Results and Conclusion: Function preservation techniques used in the harvesting of this flap will be able to cover narrow and linear defects on middle third of tibia comfortably. Size and pliability of the muscle must be assessed before initiation of harvesting of the flap. Flap harvesting is initiated by a saggital split incision to preserve maximum blood supply to the muscle. Transverse incisions may be employed to obtain the desired reach of the flap. This flap is a simple alternative for linear wounds with small transverse dimensions on middle third of the leg, where the tibialis anterior muscle is uninjured.